Pendekatan Design Science: Metode Penelitian Alternatif Bagi Mahasiswa Magister Manajemen - Stepanus, Mone (Jurnal Manajemen dan Usahawan Indonesia, 2023)
The obligation of graduate students, including Master of Management (MM) students, to publish in academic journal need to be approached wisely. Thus far, research conducted by MM students for their theses has been perceived as lacking practical contribution. This issue is also felt in business and management research in general. However, MM students are expected, in fact, to become profesionals who can offer solution to real problems faced by their organizations. The design science method could be an alternative for MM students to conduct research that is both close to practical application and still offers theoretical contribution. This article aims to introduce the design science method in research. Started with a debate in academic research, the article then explains the position of design science in the existing polarization of research approaches. The article then details what and how to conduct design science research. Finally, the article presents a guideline in conducting design science research.